2018
DOI: 10.1111/jcmm.13579
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinesis arrest and multiple centrosomes in B cell chronic lymphocytic leukaemia

Abstract: Cytokinesis failure leads to the emergence of tetraploid cells and multiple centrosomes. Chronic lymphocytic leukaemia (CLL) is the most common haematological malignancy in adults and is characterized by clonal B cell expansion. Here, we show that a significant number of peripheral blood CLL cells are arrested in cytokinesis and that this event occurred after nuclear envelope reformation and before cytoplasmic abscission. mRNA expression data showed that several genes known to be crucial for cell cycle regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Qu et al [79] detected the up-regulated expression of P21 as well as the down-regulated expression of cyclin E, demonstrating the molecular mechanism underlying ING4-induced G 1 arrest in colorectal LoVo cells. A recent study in chronic lymphocytic leukemia cells indicates that the altered expression level of ING4 contributes to regulation of the cell cycle, thereby disrupting mitosis [76]. Nevertheless, some studies have failed to show any relevant effect of ING4 in some cell lines [5,52].…”
Section: Dysregulation Of Ing4 In Tumors and Mechanisms Of Tumor Suppmentioning
confidence: 99%
“…Qu et al [79] detected the up-regulated expression of P21 as well as the down-regulated expression of cyclin E, demonstrating the molecular mechanism underlying ING4-induced G 1 arrest in colorectal LoVo cells. A recent study in chronic lymphocytic leukemia cells indicates that the altered expression level of ING4 contributes to regulation of the cell cycle, thereby disrupting mitosis [76]. Nevertheless, some studies have failed to show any relevant effect of ING4 in some cell lines [5,52].…”
Section: Dysregulation Of Ing4 In Tumors and Mechanisms Of Tumor Suppmentioning
confidence: 99%
“…Interestingly, active Ras was in one study reported to induce cytokinesis in non-adherent human fibroblasts, as analyzed by FACS [16]. Because of the difficulty in analyzing bi-nucleated cells at the cytokinesis stage using FACS without breaking the narrow cytoplasmic bridge [17, 18] uncertainty still remains regarding the ability of oncogenic RAS to promote ESCRT III-mediated abscission in detached cells. In the present study we aimed to clarify this important issue, as well as to determine the fate of bi-nucleated cells in the following cell cycle and its dependence on p53.…”
Section: Introductionmentioning
confidence: 99%